A prospective observational study on asymptomatic bacteriuria in pregnancy & its effects on maternal & perinatal outcome - K. Mounika; Pramila Gupta; Parveen Yousuff (Al Ameen Journal of Medical Sciences)
Background: Urinary tract infections (UTI) continue to be one of the most common medical conditions complicating pregnancy, with a prevalence of approximately 20% .UTI include asymptomatic bacteriuria (ASB), cystitis & pyelonephritis. The prevalence of ASB is 2% to 10% of cases. ASB prevalence and its maternal & perinatal outcomes are analysed in this study. Aim: To study the maternal and perinatal outcome of asymptomatic bacteriuria in pregnancy. Materials and Methods: This is prospective observational study done among 100 women with asymptomatic bacteriuria in pregnancy in Department of obstetrics & Gynecology, Shifaa hospital, Bangalore. Various adverse outcomes in pregnant women & neonates are observed as variables and their incidences were calculated. Results: In the present study the incidence of asymptomatic bacteriuria was observed to be more among 23 to 26 yrs, primigravida with gestational age of 12-24 weeks. Maternal & perinatal morbidities like pre eclampsia, anemia were more common and 28% of births were low birth weight i.e. <2.5 kg at birth who needed close monitoring in NICU. Majority of the study population underwent normal vaginal delivery. Antibiogram was found to be E coli, klebsiella and Staphylococcus aureus. Conclusion: Asymptomatic bacteriuria if left untreated will progress into symptomatic urinary tract infections and pyelonephritis which have an adverse maternal and fetal outcome. Early detection and treatment of ASB can prevent the adverse outcomes which can be achieved by routine screening for ASB in all antenatal patients as early as possible.